Preparation and characterization of poly (e-caprolactone)/TiO2 micro-composites - M., Shoja; K., Shameli; Ahmad @ Ayob, Mansor; Z., Zakaria (Institute of Materials Physics, 2015)
Based on XRD results, the study of crystallization of the PCL/TiO2MCs showed that TiO2MPs have significant influence on crystallization behaviour of poly (ε-caprolactone) in the PCL/TiO2MCs. The FTIR spectra indicated that the C=O of PCL shifted when TiO2MPs was added, indicating that some Van der Waals bonding between the alkyl groups of TiO2 and the ester group of PCL were formed. In comparison with the pure PCL, TGA data indicated an enhancement of thermal stability of PCL/TiO2MCs. SEM results confirmed the surface of TiO2MPs has sufficient compatibility with PCL through the link of the coupling agent between TiO2MPs and PCL, which can reduce the aggregation of TiO2MPs and improve dispersity. Transmission electron microscope (TEM) studies were performed to provide evidence for the micrometric dispersion of the TiO2MPs into PCL matrix on microscale.